Doing Well in Reforming the Labour Market? Recent Trends in Job Stability and Wages in Germany - Gianna Claudia Giannelli; Ursula Jaenichen; Thomas Rothe (Institute for the Study of Labor (IZA), 2013)
The German employment miracle, with a weak decline in employment and low unemployment during the great recession, seems to be a good example for a successful labour market reform. Nevertheless, there are concerns about rising inequality in the labour market. In this paper we analyze the quality of newly started jobs between 1998 and 2010 using a huge administrative data set which allows us to look at job durations and earnings for different groups of workers. We discuss changes in the distributions of job durations and earnings over time, and present microeconometric models controlling for individual, firm and regional characteristics. Our results show a fairly constant level of overall job stability, but decreasing real wages and rising wage dispersion over time.
Keywords: C34; C41; J31; J62; J68; 330; labour market reforms; job quality; job duration; real wages; Germany; 1998-2010